The Effectiveness of 2.5% NaOCl Irrigation and 17% EDTA against the Sealing Ability of Resin Paste - Tamara Nitya A; Nanik Zubaidah; Moch Mudjiono (Conservative Dentistry Journal, 2019)
Background: Root canal irrigation seeks the elimination of bacteria and its products from the root canal. If debris is left in the root canal, it can prohibit adaptation between obturationmaterial and root canal wall. Therefore, it can decrease the sealing ability of obturation material. Purpose: To assess the effectiveness of 2.5% NaOCl and 17% EDTA on the apical sealing ability of resin obturation paste. Method: The roots of 18 human mandibular premolar teeth were selected and the root canal was prepared using a conventional technique. Samples were irrigated with 2.5% NaOCl, and17% EDTA, and sterile aquadest (Aqua Deastilata) as a control group. Samples were filled with gutta-percha and top seal. Samples were soaked in 2% methylene blue for 48 hours to measure the depth of microleakage. Result: The mean apical leakage after irrigation with 2.5% NaOCl; 17% EDTA; and sterile aquadest in the sequence were 0.92 mm; 3.6 mm; and 8.08 mm. Conclusion: 2.5% NaOClhas less depth of microleakage than 17% EDTA. However, the depth of microleakage cannot demonstrate the exact sealing ability of the resin paste due to some factors.